(untitled) (Archaeologia Adriatica, 2017)
Nautical archaeology is a scientific discipline that studies all types of ships from the past, based on material remains, and written, iconographic and ethnographic sources. Zdenko Brusić, the pioneer of Croatian underwater archaeology, started his intensive underwater research in the 1960s, and on several occasions explored the remains of old ships. In order to keep pace with modern methodology, it has recently become clear that a standardization of the terminology used in researching historical wooden shipbuilding is necessary to be able to systematically publish the results of research activities, and to promote scholarly discussion. At the time when the subject Wooden Shipbuilding was still taught at the Faculty of Mechanical Engineering and Naval Architecture of the University of Zagreb, Teodor Bernardi wrote a textbook entitled Konstrukcija drvenih brodova (Wooden Ship Construction). His textbook served as the starting point for compiling an initial Croatian nautical archaeology glossary. This paper builds on his glossary, and is the result of intensive recent excavations of wooden ship remains in Croatian waters, which have necessarily involved the need to report and publish results in Croatian.